2016
DOI: 10.1002/lom3.10118
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and characterization of coastal dissolved organic matter by high‐performance size exclusion chromatography with ultraviolet absorption, fluorescence, and total organic carbon analyses

Abstract: Molecular size and dissolved organic carbon (DOC) distributions of dissolved organic matter (DOM) in seawater were determined qualitatively and quantitatively by high-performance size exclusion chromatography (HPSEC). To estimate the relationship between molecular size distribution and the DOC concentration of seawater DOM, seawater was desalinated with an electric dialyzer. The recent technological advancements of desalination make us possible to recover a high percentage of seawater DOM. Surface coastal seaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…In seawater, inorganic Hg­(II) speciation is thought to be mainly controlled by complexation with chloride, bromide, and DOM. Recent studies demonstrated that DOM in coastal water is dominated (≥75%) by low MW (MW ≤ 2 kDa) hydrophilic fulvic-like organic matter. , The size of these predominant DOM, based on their MW, can be estimated to be a few nanometers. Therefore, Hg­(II) complexes with these small DOM may diffuse through the gel and contribute to the observed Hg­(II) dyn fraction.…”
Section: Resultsmentioning
confidence: 99%
“…In seawater, inorganic Hg­(II) speciation is thought to be mainly controlled by complexation with chloride, bromide, and DOM. Recent studies demonstrated that DOM in coastal water is dominated (≥75%) by low MW (MW ≤ 2 kDa) hydrophilic fulvic-like organic matter. , The size of these predominant DOM, based on their MW, can be estimated to be a few nanometers. Therefore, Hg­(II) complexes with these small DOM may diffuse through the gel and contribute to the observed Hg­(II) dyn fraction.…”
Section: Resultsmentioning
confidence: 99%
“…Traditional methods focusing on DOM molecular size are typically not capturing the continuous nature of the size distribution, but relying on either operational cutoffs (e.g., tangential ultrafiltration techniques) or simplifying indices of the size spectrum (e.g., averaged molecular weight from size‐exclusion chromatography). However, Shimotori et al (2016) showed that photochemical characteristics of natural DOM depend on molecular sizes. In order to examine the continuous DOM size distribution in more detail, we applied a decomposition method that aims to utilize all the potential information contained in the size‐exclusion chromatograms.…”
Section: Discussionmentioning
confidence: 99%
“…Size‐separated DOM molecules are commonly detected and analyzed with absorbance or fluorescence detectors in size‐exclusion chromatography setups (Shimotori et al 2016). The chosen detector wavelength has also important consequences on the results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Potassium hydrogen phthalate (Kanto Chemical) was used as a standard. Additionally, molecular size distributions of DOC were measured by high-performance size exclusion chromatography (HPSEC) with total organic carbon detectors in monoplicate, according to Kawasaki et al (2011) and Shimotori et al (2016). In the HPSEC analysis, there were two peaks of weight-averaged molecular sizes (M w ) of 1.3 ± 0.1 × 10 5 Da and 2.2 ± 0.2 × 10 3 Da (n = 117), and we defined them as high-molecular-weight DOC (HMW-DOC) and low-molecular-weight DOC (LMW-DOC), respectively, in the present study.…”
Section: Sample Analysismentioning
confidence: 99%